CDKG1 Is Required for Meiotic and Somatic Recombination Intermediate Processing in Arabidopsis. Issue 4 (10th February 2020) - Nibau, Candida; Lloyd, Andrew; Dadarou, Despoina; Betekhtin, Alexander; Tsilimigka, Foteini; Phillips, Dylan W.; Doonan, John H.
Abstract : The cyclin-dependent kinase CDKG1 stabilizes recombination intermediates during male meiosis and DNA damage-induced somatic homologous recombination. Abstract: The Arabidopsis ( Arabidopsis thaliana ) cyclin-dependent kinase G1 (CDKG1) is necessary for recombination and synapsis during male meiosis at high ambient temperature. In the cdkg1-1 mutant, synapsis is impaired and there is a dramatic reduction in the number of class I crossovers, resulting in univalents at metaphase I and pollen sterility. Here, we demonstrate that CDKG1 is necessary for the processing of recombination intermediates in the canonical ZMM recombination pathway and that loss of CDKG1 results in increased class II crossovers. While synapsis and events associated with class I crossovers are severely compromised in a cdkg1-1 mutant, they can be restored by increasing the number of recombination intermediates in the double cdkg1-1 fancm-1 mutant. Despite this, recombination intermediates are not correctly resolved, leading to the formation of chromosome aggregates at metaphase I. Our results show that CDKG1 acts early in the recombination process and is necessary to stabilize recombination intermediates. Finally, we show that the effect on recombination is not restricted to meiosis and that CDKG1 is also required for normal levels of DNA damage-induced homologous recombination in somatic tissues.